A parallel auto-adaptive topology for integrated energy harvesting system. (April 2020) - Flores-Quintero, Roberto Rafael; Flores-Verdad, Guillermo Espinosa; Gonzalez-Diaz, Victor Rodolfo; Carrillo-Martinez, Luis Antonio
Abstract: This work presents a new topology for a thermal and RF energy harvesting system for integrated circuits. The system improves two circuit parameters: low start-up voltage and high-efficiency energy extraction. The high efficiency is achieved with a new parallel auto-adaptive DC-DC converter with a charge-pump based design to collect thermal energy. The low start-up voltage is possible with the assistance of a Radio-Frequency harvester circuit, resulting in a new hybrid energy harvesting architecture. The circuit was designed and fabricated with a CMOS 180 nm process, using an active area of 954  μ m × 341  μ m. The measurement results show an 87 % peak efficiency with a maximum regulated output voltage of 2 V. The minimum operating input voltage is 250 mV without the start-up circuit and 30 mV with the RF start-up circuit at 33 KHz of switching frequency.